Analisis Yuridis Hak Pasien Bayi Prematur dalam Mendapatkan Pemeriksaan Uji Tapis Wajib - Agung Zentyo Wibowo; Efrila Efrila; Anis Retnowati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the legal rights of premature infants to access mandatory screening examinations from a juridical perspective. Premature infants are a highly vulnerable group at risk of permanent complications, making early screening a fundamental medical necessity. However, findings indicate a significant legal gap within Indonesia’s national regulations, as Law Number 17 of 2023 on Health only provides general provisions on newborn screening without specific technical guidelines for premature infants. Regulatory fragmentation, inconsistent implementation across healthcare facilities, and limited integration with the National Health Insurance (BPJS Kesehatan) scheme have led to disparities in service delivery. The juridical analysis reveals that failure to conduct mandatory screening may result in criminal, civil, and administrative liability, as well as violations of children’s rights to optimal health. Therefore, this study recommends legal reform through comprehensive implementing regulations, evidence-based clinical guidelines, intersectoral regulatory harmonization, and capacity-building for healthcare professionals. Public education and national epidemiological research are also essential to inform policy development. Ultimately, regulatory reform is expected to ensure the fulfillment of premature infants’ rights to equitable and sustainable access to optimal healthcare services.